Criminal Accountability for Perpetrators of Distributing Child Pornography Content on Social Media - Maliha, Rohatul; Hidayati, Rahmatul; Parmono, Budi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid development of information and communication technology has facilitated the spread of criminal activities in digital environments, including the distribution of child pornography on social media platforms. Specific Background: Children, as rights-bearing legal subjects requiring special protection, are increasingly exposed to sexual exploitation within open and anonymous online spaces, raising significant legal concerns in Indonesia. Knowledge Gap: Although multiple legal instruments regulate this crime, there remains limited clarity regarding the practical implementation and coordination of these regulations in addressing accountability. Aims: This study aims to analyze the existing legal frameworks and examine the forms of criminal accountability for perpetrators distributing child pornography content on social media. Results: Using a normative juridical method with statutory and conceptual approaches, the findings indicate that Indonesia’s legal provisions are normatively comprehensive and have been strengthened through various laws and regulations; however, enforcement faces persistent challenges, including difficulties in digital evidence collection, perpetrator tracking, and inter-agency coordination. Novelty: The study provides an integrated examination of multiple legal instruments alongside practical enforcement barriers in the digital context. Implications: Strengthening law enforcement capacity and improving regulatory synergy are necessary to ensure effective and just child protection in digital spaces. Highlights: Legal provisions addressing the issue are comprehensive and increasingly reinforced. Practical challenges arise in evidence handling, perpetrator identification, and institutional coordination. Strengthened enforcement capacity and regulatory alignment are required for improved child protection. Keywords: Criminal Accountability, Child Pornography, Social Media.